US Taiwan Policy during the George W. Bush Administration (2001-2009) - Lian Deng, Ben (Revista Neiba, Cadernos Argentina Brasil, 2019)
The purpose of this article is to analyze the United States’ (US) Taiwan policy during the George W. Bush administration (2001-2009)—specifically, how Washington actively opposed Taiwanese independence during this period. After the Korean War (1950), the US’s official policy on Taiwan was to “neutralize” and prevent war across the Taiwan Strait, thereby maintaining the status quoin the region. During the 1950´s and 1960´s, the US successfully prevented Chinese attempts to invade Taiwan. However, the dynamic of the cross-strait relations changed drastically in the 1990´s, following Taiwan’s political liberalization and the emergence of the Taiwanese independence movement. During the George W. Bush administration (2001-2009), Taiwan was ruled by the pro-independence Chen Shui-bian (2000-2008), which increased cross-strait tensions. In order to satisfy its own geopolitical interests, the US actively denied support to this movement, boycotting Chen´s attempts to declare Taiwan´s independence. This paper concludes that the core of the US’s Taiwan policy is to prevent alteration of the status quo or threat of war in the region, while using the “Taiwan Card” as a bargaining chip in bilateral negotiations with China.